Marie Sallé and the Development of the Ballet en action - McCleave, Sarah (Journal of the Society for Musicology in Ireland, 2007)
This article identifies the role played by acclaimed dancer and choreographer Marie Sallé (1707-56) in the development of the ballet en action. This is done by making a lexicographical study of key terms (particularly action, character, and intrigue) found in the writings of contemporaries who praised the dancer, such as revolutionary choreographer Jean-Georges Noverre and critic Louis de Cahusac. This lexicographical study is then applied to some of Sallé’s important creative works of the mid-1730s, including Handel’s Terpsichore (London, 1734), a revival of André Campra’s L’Europe galante (Paris, 1736), the ‘Ballet des Fleurs’ from Rameau’s Les Indes galantes (Paris, 1735) as well as Bacchus and Ariadne (London, 1734).